The incidence of vesicoureteral reflux in children with urinary tract infections - Gabriel C. Dragan (Amaltea Medical Publishing House, 2019)
Introduction. Urinary tract infections (UTI) are the most frequent bacterial infection in children. The prevalence of UTIs depend on age and sex and it is higher in boys in the first year of life. After one year of age the prevalence is higher in girls. UTIs can be the first sign of congenital anomalies of the urinary tract and kidney, vesicoureteral reflux (VUR) being the most frequent, especially in children under 2 years of age. Voiding cystouretrography (VCUG) is the "gold standard" in diagnosing and classifying VUR. Materials and methods. This study is a retrospective analysis of the patients admitted for VCUG in "Grigore Alexandrescu" Emergency Clinical Hospital for Children, Bucharest, between 1st January 2015 and 31st December 2017. Results. There were 298 VCUGs performed in patients with a history of at least one episode of febrile UTI. 83/298 (27,9%) patients were diagnosed with VUR, 36/298 (12.1%) with bilateral VUR. We observed a negative trend in the incidence of VUR with age (p<0.05). In 296 cases renal bladder ultrasound (RBUS) was available. 179 patients had negative RBUS, 35 (19,5%) of them being diagnosed with VUR, 9 patients (5%) with dilating VUR. In patients under 2 years of age the incidence of VUR was 36.4% (43/118). The incidence of VUR in girls under 2 years of age was 49% (25/51), with 12/51 girls (23.5%) having dilating VUR. In boys under 2 years of age the incidence of VUR was 26.9% (18/67), and 20.9% (14/67) for dilating VUR. Conclusions. Although the latest guidelines recommend VCUG only in selected cases, this imaging study remains indispensable in diagnosing VUR. We consider that an individualized approach must be applied in the management of children with a history of UTI.